Play and Game Based Learning in Coding Education: A Bibliometric Mapping Toward Integrated Computational Thinking, Digital Literacy, and Psychomotor Outcomes in Primary Schools - Laksana, Dek Ngurah Laba; Gelu, Afrianus; Suparmi, Ni Wayan (Jurnal Pendidikan Jompa Indonesia, 2025)
This study maps the thematic landscape of coding education research in primary schools through a bibliometric keyword co-occurrence analysis to clarify dominant emphases and identify underexplored directions for instructional design. Using a structured search strategy that combines coding/programming terms with play/game-based learning and learning-outcome constructs, the analysis reveals five major clusters that collectively highlight a strong concentration on computer science learning contexts (e.g., course implementation, effectiveness, engagement, and problem solving) and on experimental, digitally mediated interventions particularly digital game-based approaches aimed at improving computational thinking, motivation, and performance. Across clusters, the literature shows a consistent tendency to foreground cognitive and affective outcomes, while explicit integration of digital literacy as a comprehensive competence and psychomotor development as an equivalent educational target appears comparatively limited. The mapped themes also suggest that value-embedded and culturally grounded design principles are less frequently articulated as systematic, transferable frameworks, despite their relevance for context-sensitive learning in diverse settings. Based on these findings, the study proposes a future research agenda that moves beyond predominantly digital-game and experiment-centered trajectories by strengthening integrative outcome frameworks (computational, digital, and psychomotor domains), advancing culturally grounded design principles, and developing replicable unplugged play-based models such as the Bodhuleke Bot approach within an Educational Design Research pathway.